Reducing senior secondary school studetns' mathematics anxiety through brain-based instructional strategy: a study in school effectiveness (2011)
One of the indicators of school effectiveness is the sate of learning environment.Learning enivironment could be physical or psychological (anxiety). This study focuses on the later. If the learning environment is not conducive, studetns are not likely to learn well, thus failure rate may be high. One of the psychological learning environments which is potent is causing high failure rate in mathematics is studetns' anxiety. The students' anxiety in mathematics is likely to have its root from how the subject is taught. This study, therefore, examines ways of reducing senior secondary school students' anxiety in mathematics using brain-based instructional strategy. The study adopted a quasi experimental design with pre test-post test control groups. Two instruments: response (mathematics anxiety scale) and stimulus (experimental package) were used to collect data. The result shows that studetns exposed to brain-based instructional strategy had their anxiety level in mathematics reduced than those in the control group. It to have its root from how the subject is taught. This study, therefore, recommended that teachers should use brain-based instructional strategy in teaching. moreover, because brain-based instructional strategy is relatively new, teachers should be taught to use it in teaching mathematics in schools since it has the potential to reduce studetns' mathematics anxiety.